2016
DOI: 10.1021/acssuschemeng.6b01890
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Polymerization Behavior of the Vinyl Monomers from Plant Oil Triglycerides

Abstract: A one-step method of plant oil direct transesterification was used to synthesize new vinyl monomers from sunflower (SFM), linseed (LSM), soybean (SBM), and olive (OVM) oils. The degree of unsaturation in plant oil fatty acids was used as a criterion to compare the free radical polymerization behavior of new monomers. The number-average molecular weight of plant oil-based homopolymers synthesized in toluene in the presence of AIBN at 75 °C varies at 11 000–25 000 and decreases as follows: poly­(OVM) > poly­(SFM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 30 publications
4
82
0
Order By: Relevance
“…Recently, we developed a one-step method of plant oil direct transesterification into vinyl monomers for free radical polymerization and copolymerization [11][12][13]22]. It was demonstrated that the rate of POBM homopolymerization, where chain propagation coexists with chain transfer reaction on monomers, is determined primarily by the amount of unsaturation in each plant oil triglycerides.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we developed a one-step method of plant oil direct transesterification into vinyl monomers for free radical polymerization and copolymerization [11][12][13]22]. It was demonstrated that the rate of POBM homopolymerization, where chain propagation coexists with chain transfer reaction on monomers, is determined primarily by the amount of unsaturation in each plant oil triglycerides.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the rate of POBM homopolymerization, where chain propagation coexists with chain transfer reaction on monomers, is determined primarily by the amount of unsaturation in each plant oil triglycerides. In the next step, stable latexes containing up to 50wt% of plant oil-based content were synthesized using miniemulsion copolymerization of POBM with their petroleum-based counterparts [13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations